Development of Cold Brew Ginger Drink As A Non-Alcoholic Beverage Innovation - Johannes Kurniawan; Christoforus Djohan Santosa (Journal of Social Research, 2026)
Wedang ginger is a traditional Indonesian beverage rich in health benefits; however, in Grendeng Pulo Karawaci Village, Tangerang Regency, its production is still limited to hot form, which is less appealing to young consumers. The main problems include limited product innovation, overly spicy ginger flavor, rapid loss of aroma due to traditional extraction techniques, and a shelf life of less than 3 days in a humid tropical climate, which risks contamination and a decline in hygienic quality. This research aims to develop wedang ginger cold brew as an innovation in fresh non-alcoholic beverages, through a cold extraction process (cold brew) to produce a mild flavor, long-lasting aroma, and shelf life of up to 11 days. The implementation method is participatory, including problem identification through observation, cold brew production prototypes (soak ginger for 12-24 hours at room temperature, refrigerate for 5 days, strain, and adjust flavor), educational workshops, as well as sensory evaluation and pre-post questionnaires. This innovation also includes product variations such as ginger basil lemon, ginger cold brew milk, and others to enhance appeal. The expected outcomes are that 100% of workshop participants can independently adopt the cold brew method, a minimum product shelf life of 7-11 days, and an increase in young consumer interest by 70%. The benefits of the research include village economic empowerment through diversification of herbal non-alcoholic beverage businesses, preservation of local culture, and contributions to public health with natural, hygienic products